August Wilhelm Du Roi journal - Du Roi, August Wilhelm
Journal (2 volumes; 1776 February 22-1779 March 7). Contains diary entries while Du Roi was serving with German troops in British General John Burgoyne's army, a description of the march of British prisoners from Boston, Mass., to Virginia in 1778, general orders (1777 July 12-August 11), and an order of battle for the army of Burgoyne at Albany, N.Y. (1777).
German officer serving in the British army during the American Revolution. Also known as Du Roi (or Duroi) the Elder.
Collection material in English.
Keywords: Burgoyne, John, -- 1722-1792.; Albany (N.Y.) -- History -- Revolution, 1775-1783.; Boston (Mass.) -- History -- Revolution, 1775-1783.; Massachusetts -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; Virginia -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Participation, German; United States -- History -- Revolution, 1775-1783 -- Prisoners and prisons; Army officers, British; Army officers, German